Electronic search engine for housing exchange as a tool in the management of the municipal housing stock - Dziadkiewicz, Michał; Cichowski, Paweł (Business Informatics, 2017)
The article is devoted to the problem of using information technologies in themanagement of the municipal housing stock. In particular the impact of the use of these technologieson the effectiveness of the recovery of overdue municipal receivables due to the leaseof communal premises and the improvement in the living and financial situation of the tenantswas analyzed. In order to demonstrate the practical use of information technologies in managingthe municipal housing stock and their effectiveness in the aforementioned area, the exampleof the electronic search engine for exchanging apartments, which was launched by theDepartment of Housing Management Social Housing Association in Czestochowa LLC(ZGM TBS Sp. z o.o.), was used. The article also discusses the influence of the search engineon credit management of the Municipality of Czestochowa and on the effectiveness of usingits housing stock, as well as using the engine as a tool in debt relief programs for the tenants.In addition to the indicated issues, the article characterizes the systemic status of municipalitiesand their tasks in the management of their housing stock, as well as in meeting the housingneeds of the local community. The main purpose of the article is to indicate the positive influenceof the applied technologies on debt restructuring and on increasing the subjectivity andindividuality of tenants
Informatyka Ekonomiczna = Business Informatics, 2017, Nr 2 (44), s. 48-59
Keywords: information technologies; management of the municipal housing stock; credit management; zarządzanie mieszkaniowym zasobem gminy; zarządzanie wierzytelnościami; technologie informatyczne